THE INFLUENCE OF COMPLIANCE WITH ISLAMIC ECONOMIC PRINCIPLES ON THE PERFORMANCE OF HNI MULTI LEVEL MARKETING (MLM) DISTRIBUTORS, EAST BEKASI BRANCH - Jauhari, Muhammad Sofwan (STAI Asy-Syukriyyah, 2025)
Sharia-based Multi-Level Marketing (MLM) is increasingly developing as a business alternative that aligns with Islamic economic principles. However, challenges remain in ensuring compliance with these principles and their impact on distributor performance. This study aims to analyze the influence of compliance with Islamic economic principles on the performance of distributors at HNI Bekasi Timur Branch. The Islamic economic principles examined include interest-free transactions, honesty in promotion, price transparency, contract compliance, and fairness in profit distribution. This research employs a quantitative method with a simple linear regression approach. Data were collected through questionnaires distributed to HNI Bekasi Timur Branch distributors, and their validity and reliability were tested. The results indicate that compliance with Islamic economic principles significantly affects distributor performance, with an R Square value of 0.587, meaning that 58.7% of the variation in distributor performance can be explained by the variable of compliance with Islamic economic principles. The positive regression coefficient (B = 0.745, p = 0.000) shows that the higher the compliance with Islamic economic principles, the better the distributor performance. A significant F-test (p = 0.000) also indicates that the model used is valid in explaining the relationship between the two variables. Thus, the application of Islamic economic values in business strategies has been proven to enhance the performance and competitiveness of sharia-based MLM distributors.